Administrative Leave of Priest Accused of Sexual Abuse: Canon 1722 - Daly, Brendan (CLSA advisory opinions, 2001-2005, 2001)
A priest in our diocese has been placed on administrative leave, as a result of being accused of having sexually abused a minor. What are the effects of this action taken by the bishop? Since our diocese is not in the United States, what significance, if any, do the American Essential Norms have on this action of the bishop?